SCENARIOS OF AGRICULTURAL POLICY IN BOSNIA ANDHERZEGOVINA AFTER ACCESS TO THE EUROPEAN UNION (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Bosnia and Herzegovina’s clear aspirations for accession to the European Union entail gradual alignment with measures and instruments of the EU’s Common Agricultural Policy during the pre-accession period, aimed at preparing the country for integration into the complex institutional and legislative framework of the EU CAP. To monitor this process, an assessment of total support to producers in Bosnia and Herzegovina has been calculated using relative indicators: TTP (Total Transfers to Producers), NRP (Nominal Protection Rate), and NRA (Nominal Assistance Rate), which enable monitoring of agricultural policy and, based on that, an assessment of Bosnia and Herzegovina’s standards alignment with EU CAP standards. The calculations have shown that the most significant changes are expected in the support structure, moving towards further reduction of direct support per output, strengthening area/headage payments, and harmonizing amounts per unit of measurement as the first step towards production-related payments currently in force in the EU. In addition to indicators, an assessment of income for Bosnian producers after accession to the EU has been calculated. By simulating Bosnia and Herzegovina’s accession to the EU, answers have been obtained regarding the application of the EU CAP and possible implications of implementing a harmonized agricultural policy, which could be beneficial for decision- makers in future pre-accession and accession negotiations when opening agriculture chapters.